Improving Control of Gene Therapy-Based Neurotrophin Delivery for Inner Ear Applications - St. Peter, Madeleine; Brough, Douglas E.; Lawrence, Anna; Nelson-Brantley, Jennifer; Huang, Peixin; Harre, Jennifer; Warnecke, Athanasia; Staecker, Hinrich (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Survival and integrity of the spiral ganglion is vital for hearing in background noise and for optimal functioning of cochlear implants. Numerous studies have demonstrated that supplementation of supra physiologic levels of the neurotrophins BDNF and NT3 by pumps or gene therapy strategies supports spiral ganglion survival. The endogenous physiological levels of growth factors within the inner ear, although difficult to determine, are likely present at extremely low within the normal inner ear. Thus, novel approaches for the long-term low-level delivery of neurotrophins may be advantageous. Objectives: Evaluation of the long-term effects of gene therapy-based low-level neurotrophin supplementation on spiral ganglion survival. Using an adenovirus serotype 28 derived adenovector delivery system, the herpes latency promoter, a weak, long expressing promoter system, has been used to deliver the BDNF or NTF3 genes to the inner ear after neomycin-induced ototoxic injury in mice. Results: Treatment of the adult mouse inner ear with neomycin resulted in acute and chronic changes in endogenous neurotrophic factor gene expression and led to a degeneration of spiral ganglion cells. Increased survival of spiral ganglion cells after adenoviral delivery of BDNF or Ntf3 to the inner ear was observed. Expression of BDNF and NT3 could be demonstrated in the damaged organ of Corti after gene delivery. Hearing loss due to overexpression of neurotrophins in the normal hearing ear was avoided when using this novel vector-promoter combination. Conclusions: Combining supporting cell specific gene delivery via the adenovirus serotype 28 vector with a low strength long expressing promoter potentially can provide long term neurotrophin delivery to the damaged inner ear.